Application of Sharia Accounting in Recognizing Income on Murabahah Financing and Compliance with PSAK 102 at Bank Syariah Indonesia - Nurul Aini Azizah; Diana Djuwita; Alvien Septian Haerisma (Politeknik Siber Cerdika Internasional, 2023)
Murabahah financing products at Bank Syariah Indonesia have increased, this is because murabahah financing is consumptive and flexible financing. The treatment of Islamic accounting which includes recognition, measurement, presentation, and disclosure in murabahah financing based on Statement of Financial Accounting Standards (PSAK) 102. The amount of profit obtained by Bank Syariah Indonesia from murabahah financing depends on the method of income recognition used by referring to the applicable standards. This study aims to determine the application of PSAK 102 to the treatment of murabahah accounting and income recognition methods used by Bank Syariah Indonesia. The method used in this study is a qualitative method with a case study approach. The results of this study as a whole the treatment of sharia accounting in murabahah transactions at Bank Syariah Indonesia are in accordance with PSAK 102 concerning murabahah accounting both in terms of recognition, measurement, presentation and disclosure. Meanwhile, the recognition of its income by Bank Syariah Indonesia uses the annuity method because it is considered more aggressive and more profitable.